U.S. Foreign Policy and Southeast Asia: From Manifest Destiny to Shared Destiny - Chew, Emrys (2016)
From post-colonial state to global superpower, America’s relations with Southeast Asia—as with the rest of the world—have been driven by a peculiar sense of “manifest destiny.” Founded upon such transcendent values as “life, liberty, and the pursuit of happiness,” the United States as champion of those values in the world has, time and again, rightly or wrongly, made a case for American exceptionalism if not interventionism. In its quest for security and prosperity, and in little over two centuries of its existence, the United States attained a measure of global authority surpassing George Washington’s loftiest aspirations. Yet America’s global transformation into a new “empire of liberty,” with all its inherent ambiguities of power, did not deliver the freedom from fear that Washington had envisioned: from Pearl Harbor to Ground Zero, from Vietnam to Afghanistan. Ironically using instruments of American-led globalization—commercial airliners, the Internet, and cell-phones—against those other symbols of U.S. global dominance, the Islamic extremist terror attacks of September 11th 2001 have shown that even “hyperpower” is vulnerable at its metropolitan core. At the “periphery” also, just as the United States has sought to refashion nations abroad in its image—from past ages of Western imperialism, world wars and decolonization, through to the Cold War and the “war on terror”—the diverse nations that constitute Southeast Asia have played their part in shaping the imperatives and dynamics of U.S. foreign policy. These cross-cultural interactions, perceptions and reactions, reveal both the extent and the limits of American power in the region. This historical study examines the distinctive phases and emphases of U.S. foreign policy in Southeast Asia, as well as evolving Southeast Asian perspectives on U.S. foreign policy.